Analisis Dampak Pertumbuhan Pajak Hotel Dan Restoran Terhadap Peningkatan Pendapatan Asli Daerah Kota Bandung Sebelum dan Sesudah Pandemi Covid-19 (2019–2023) - Nelsy Kusumaningrum; Citra Sukmadilaga (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
Locally-Generated Revenue (PAD) is a key indicator of a region’s fiscal independence, with regional taxes-particularly Hotel Tax and Restaurant Tax-being the largest contributors. These taxes present significant potential, especially in cities with thriving tourism and culinary sectors such as Bandung. This study analyzes the effect of Hotel Tax and Restaurant Tax revenues on Bandung City’s PAD for the period of 2019–2023 using multiple linear regression based on secondary data. The results show that, partially, Hotel Tax does not have a positive effect, whereas Restaurant Tax has a positive effect on Bandung’s PAD. However, when analyzed simultaneously, both variables have a positive effect on the PAD of Bandung City.